1994
DOI: 10.1016/0020-7292(94)90760-9
|View full text |Cite
|
Sign up to set email alerts
|

External cephalic version after previous cesarean section—a clinical dilemma

Abstract: External cephalic version to vertex presentation after previous cesarean section was successful in all 11 carefully selected patients. No untoward effects were noted, and no signs of scar dehiscence were found. The safety and efficacy of this procedure after previous cesarean delivery should be examined further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 11 publications
0
28
1
1
Order By: Relevance
“…14,15,13 Of these, 54 to 76% had a successful vaginal delivery, and there was no reported increase in the rate of uterine rupture or dehiscence. In our own study, the higher median parity likely increased the success of subsequent vaginal delivery in both the groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15,13 Of these, 54 to 76% had a successful vaginal delivery, and there was no reported increase in the rate of uterine rupture or dehiscence. In our own study, the higher median parity likely increased the success of subsequent vaginal delivery in both the groups.…”
Section: Discussionmentioning
confidence: 99%
“…14 , Flamm 15 and Schachter et al 13 reported successful ECV in a total of 105 women with prior cesarean delivery, with rates ranging from 65 to 100%. 14,15,13 Of these, 54 to 76% had a successful vaginal delivery, and there was no reported increase in the rate of uterine rupture or dehiscence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Use of antepartum transabdominal amnioinfusion to facilitate external cephalic version after initial failure has met with success, 40 and use of external cephalic version with spinal anesthesia 41 or tocolysis at 37 weeks or later appears to decrease maternal discomfort and facilitate manipulation, even allowing for external version after previous cesarean section in carefully selected patients. 42,43 Cesarean Section When a fetus is in breech presentation, the second line of prevention is to strive to forestall the potential complications of vaginal delivery by accomplishing a cesarean section when indicated. 5-8 Table 42-1 lists some of the indications for a cesarean delivery.…”
Section: External Cephalic Versionmentioning
confidence: 99%
“…Pratique de la version par manoeuvre externe (VME) sur utérus cicatriciel Elle n'est pas contre-indiquée (Encadré 5). Plusieurs études (rétrospectives et portant sur de petits effectifs) ont montré l'efficacité et l'innocuité de la VME en cas d'utérus cicatriciel [38][39][40][41][42][43][44]. Pour Flamm et al [41], le taux de réussite des VME est égal à celui des femmes sans antécédent de césarienne (82 % de réussite de la VME et 65 Encadré 5.…”
Section: Les Cas Particuliersunclassified